Persepsi Gen-Z terhadap Ketahanan Pangan di Kabupaten Rejang Lebong - Anadiya Pingki; Dodi Aprianto; Mira Yanuarti (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2024)
The younger generation plays an important role in agricultural development. Based on the Central Statistics Agency (2020), the most popular jobs for young people aged 16–30 years in the last 5 years are the Services sector, followed by Manufacturing and Agriculture. Food security in Rejang Lebong Regency is a multifaceted issue influenced by various factors including agricultural practices, economic conditions, and government policies. The purpose of this study was to determine Gen-Z's perception of Food Security in Rejang Lebong Regency. The respondents of this study were Gen-Z who were in the birth range of 1997-2012. Likert Scale Analysis was used in this study. Gen-Z's level of understanding of food security is quite good, this is known by the average value of this indicator, which is 4.11. Access and availability of food are important things that can guarantee food security with an average indicator value of 3.95. For food consumer behavior, it is an indicator related to Gen-Z consumption so that it can support food security with an average indicator value of 4.01. So it can be concluded that Gen-Z's perception of food security is in the average range of 3.90 with the conclusion that Gen-Z agrees and understands about food security in Rejang Lebong Regency.